E-Commerce and Its Impact on Consumer Buying Behavior: A Study with Reference to Retail Industry in Bangalore - Pathan, Mr. Firozkhan.I.; T, Dr. Bharathi; Uniyal, Dr. Mahesh (The journal of contemporary issues in business and government, 2022)
The main goal of the paper is to obtain quantitative describing the actuality of E-Commerce shopping in the case of the Retail Industry in Bangalore city. Online consumer buying behavior is not like a physical market having ability to touch, analyze, and thereafter shop the products. This study explores the effect of few variables, derived from existing literature. Those variables are perceived benefits, domain specific innovativeness, and shopping orientations, i.e., impulse- purchase orientation, brand orientation and quality orientation in E-Commerce companies (ebay, Amazon, Flipkart). For the study purpose data was collected by mean of the questionnaires. The findings indicated that domain specific innovativeness and shopping orientations have positive impact on consumers’ buying behavior towards E-Commerce. Therefore, consumers are showing an interest to online shopping because of recent development of retail industry in Bangalore city.